2017
DOI: 10.5830/cvja-2017-006
|View full text |Cite
|
Sign up to set email alerts
|

New World’s old disease: cardiac hydatid disease and surgical principles

Abstract: SummaryBackground:Hydatid cyst is a parasitic disease caused by infection with the Echinococcus granulosus tapeworm larva. It is a major public health problem in endemic regions. Cardiac involvement of the disease is rare.Methods:Between 1985 and 2015, 12 patients were admitted to our clinic with a possible diagnosis of cardiac hydatid disease. Of these patients, six (50%) were male and six (50%) were female. Mean age of the patients was 42.6 years.Results:The most common location of cardiac hydatid disease wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
7
0
3
Order By: Relevance
“…Malamou-Mitsi et al 7 also have reported a case in which the cyst was found intact; they suggested that the death seemed to be due to fatal left ventricular arrhythmias. Singh et al 18 reported a case of a 57-year-old man who presented with syncope due to ventricular tachycardia, and imaging revealed a right ventricular hydatid cyst. In our case, although no allergic signs were observed, anaphylactic shock cannot be excluded from the scope of mechanisms of death beyond pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malamou-Mitsi et al 7 also have reported a case in which the cyst was found intact; they suggested that the death seemed to be due to fatal left ventricular arrhythmias. Singh et al 18 reported a case of a 57-year-old man who presented with syncope due to ventricular tachycardia, and imaging revealed a right ventricular hydatid cyst. In our case, although no allergic signs were observed, anaphylactic shock cannot be excluded from the scope of mechanisms of death beyond pulmonary embolism.…”
Section: Discussionmentioning
confidence: 99%
“…The mature worm inhabits the intestines of the dog and humans are accidental hosts in their life cycle. Hydatid cysts can develop anywhere in the human body, predominantly in the lung and the liver 3 , 4 . Cardiac involvement is very scarce, even in endemic regions, and its clinical evolution is asymptomatic until acute complications or a fatal outcome occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Only 10% of cardiac hydatid cyst patients are symptomatic [ 6 ]. The disease remains silent for years, due to the slow increase in cyst diameter (about one to 1.5 cm per year) [ 7 ]. Depending on its location, the enlargement of the cyst may lead to the right or left ventricular outlet obstruction, valvular insufficiency or stenosis, cardiac failure, compression of coronary arteries, arrhythmia, or atrioventricular and intraventricular blocks [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Distintas series muestran variabilidad respecto a la frecuencia en la localización de los quistes, predominando la ubicación en el ventrículo izquierdo (47% -75%), ventrículo derecho (15% -41,7%) 7 -10 y otras ubicaciones menos frecuentes como el tabique interventricular, pericardio, arteria pulmonar y aurícula derecha. Existe una amplia gama de presentaciones clínicas, desde pacientes asintomáticos en quienes solo constituye un hallazgo 10 , hasta pacientes que presentan manifestaciones como disnea, arritmias, insuficiencia cardíaca 8,9 , signos electrocardiográficos de isquemia, alteraciones en el segmento ST y onda T 11 , dolor precordial con electrocardiografía normal 12 , fiebre 13, 14 y síncope 14,15 . El estudio diagnóstico, basado en el nivel de sospecha y la disponibilidad de recursos, puede incluir serología, electrocardiografía, estudios de imágenes como radiografía de tórax, tomografía computarizada, ecocardiograma transesofágico y transtorácico, angiografía coronaria y resonancia magnética 7 -9, 11 -13, 16 .…”
Section: Discussionunclassified